2016
DOI: 10.1007/s11095-016-2061-7
|View full text |Cite
|
Sign up to set email alerts
|

SPECT-CT Comparison of Lung Deposition using a System combining a Vibrating-mesh Nebulizer with a Valved Holding Chamber and a Conventional Jet Nebulizer: a Randomized Cross-over Study

Abstract: This study demonstrated the high superiority of the new system combining a vibrating-mesh nebulizer with a valved holding chamber to deliver nebulized particles into the lungs as comparted to a constant-output jet nebulizer with a corrugated tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 46 publications
9
41
1
Order By: Relevance
“…While efficient bronchodilation was observed with such doses [ 51 , 52 ], reaching therapeutic levels of antibiotics may be more challenging. These values are low in comparison with that reported in spontaneously breathing patients using similar models of jet or vibrating-mesh nebulizer (15 − 35% ND) [ 53 56 ]. Historically, mechanical ventilation has been considered to be a barrier to drug delivery [ 17 , 29 ].…”
Section: Discussioncontrasting
confidence: 65%
“…While efficient bronchodilation was observed with such doses [ 51 , 52 ], reaching therapeutic levels of antibiotics may be more challenging. These values are low in comparison with that reported in spontaneously breathing patients using similar models of jet or vibrating-mesh nebulizer (15 − 35% ND) [ 53 56 ]. Historically, mechanical ventilation has been considered to be a barrier to drug delivery [ 17 , 29 ].…”
Section: Discussioncontrasting
confidence: 65%
“…Prior to our project no clinical outcome comparisons between VMN and JN had been reported. However, scintigraphy data had suggested greater efficiency of drug delivery associated with the VMN as compared to JN [1,7]. A review of various meta-analyses and RCTs (involving 394 trials) comparing clinical outcomes of inhaled drugs (beta agonist, anticholinergic and corticosteroid) with nebulizers, pMDI, pMDI with spacer and DPI (dry powder inhalers) showed no difference between devices in efficacy outcomes in any patient group, including the ED [8].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these studies demonstrating greater efficiency of drug delivery, we expected that a higher dose of bronchodilator would be delivered in patients with acute respiratory distress with the VMN [1,5,7]. This project was designed to help evaluate a new nebulizer that the hospital was considering expanding the use of.…”
Section: Introductionmentioning
confidence: 99%
“…7,24 However, the main effect of the holding chamber is not to decrease the particle size of the aerosolized medication but to hold the nebulized aerosol from release to the surrounding area. 26 The urinary data from the in vivo study showed similar results. The Solo-holding chamber significantly increased the amount of drug excreted over a 24-h period after inhalation by 1.8-fold (P ϭ .02) and the amount of drug excreted in the first 30 min by 1.3-fold (P ϭ .034) compared with the Solo-T-piece.…”
Section: Discussionmentioning
confidence: 55%